Systematic Review of Back-Support Exoskeletons and Soft Robotic Suits - Ali, Athar; Fontanari, Vigilio; Schmoelz, Werner; Agrawal, Sunil K. (Frontiers in Bioengineering and Biotechnology, 2021)
Lower back pain and musculoskeletal injuries are serious concerns for workers subjected to physical workload and manual material handling tasks. Spine assistive exoskeletons are being developed to support the spine and distribute the spine load. This article presents a detailed up-to-date review on the back support exoskeletons by discussing their type (Active/Passive), structure (Rigid/Soft), power transmission methods, weight, maximum assistive force, battery technologies, tasks (lifting, bending, stooping work), kinematic compatibility and other important features. This article also assesses the back support exoskeletons in terms of their ability to reduce the physical load on the spine. By reviewing functional and structural characteristics, the goal is to increase communication and realization among ergonomics practitioners, developers, customers, and factory workers. The search resulted in reviewing 34 exoskeletons of which 16 were passive and 18 were active. In conclusion, back support exoskeletons have immense potential to significantly reduce the factors regarding work-related musculoskeletal injuries. However, various technical challenges and a lack of established safety standards limit the wide adaptation of exoskeletons in industry.